Maternal and Neonatal Characteristics in Obstetric Intensive Care Unit Admissions. Issue 4 (December 2020) - Seppa¨nen, P.; Sund, R.; Uotila, J.; Helminen, M.; Suominen, T.
Abstract : ( Int J Obstet Anesth . 2020;41:65–70) The World Health Organization defines severe acute maternal morbidity as "a woman who nearly died, but survived a complication that occurred during pregnancy, childbirth or within 42 days of termination of pregnancy." Intensive care unit (ICU) admission resulting from maternal morbidity is most commonly associated with hemorrhage-related cardiovascular instability and severe preeclampsia. This retrospective register-based study from January 2007 to December 2011 held 3 objectives: (1) to evaluate the course of pregnancy and delivery for obstetric patients admitted to ICU, (2) discern the health status of infants born to those women, and (3) comparison of the results with reference data on Finnish parturients and infants.